Pengaruh Profitabilitas Terhadap Strukitur Modal Pada Perusahaan Asam Tbk Tahun 2013-2022 - Eriana Sepang; Dina Ramba; Jemi Pabisangan Tahirs (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The question of this researceh is wheter profitability affects the capital structure of pt. Asam tbk in 2013-2022. The purpose of this researceh is to determine the effect of profitabilty on the capital strukture of pt asam tbk in 2013-2022. This research is a type of quantitative research. The type of data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange. Profitability is calculated using the Return On Equity Ratio (ROE) formula, namely by comparing profit after tax an Equity and capital structure is calculated using Debt to Equity Ratio (DER) formula, which is comparing total debt with equity. The data analysis technique used is simple linear regression analysis. The results of this study indicate that partially profitability has no effect on capital structure.